Avaliacào da gestão lntegrada de resíduos sólidos do município de olho d'água dó Borges/RN, com base na utillzaçâo de indicadores de sustentabilidade - Muniz, Elifran Dias (2024)
After the implementation of the National Solid Waste Policy, through Federal Law 12,305, of August 2010, which was processed in the National Congress for almost 20 years, changing outdated structures and reviewing previous approaches taken by public authorities to address the problem of solid waste, the subject gained more attention. Before that, Brazilian cities had an ineffective management model, promoted by the lack of efficient public policies, which resulted in high public spending and limited social reach. This lack of management has caused several negative effects on the environment, public health and social issues, with regard to the growing number of people living informally and surviving by working with solid waste. The main objective of this work is to evaluate management through a set of sustainability indicators and propose a series of recommendations aimed at municipal managers. These recommendations can be used by managers as alternatives to develop more universal municipal management, as established by the Brazilian legal framework. The results obtained prove that Municipality of Olho d'Água do Borges. For the most part, it presents unfavorable or very unfavorable management trends. With this in mind, the municipality must seek alternatives that make it possible to meet the requirements imposed by legislation, with special attention to the treatment and final disposal of waste, in addition to the creation of social policies that cover the actors involved in the solid waste chain, promoting training, appreciation and guaranteeing quality of life.